Electrode pooling can boost the yield of extracellular recordings with switchable silicon probes - Kyu Hyun Lee; Yu-Li Ni; Jennifer Colonell; Bill Karsh; Jan Putzeys; Marius Pachitariu; Timothy D. Harris; Markus Meister (Nature Communications, 2021)
Silicon probes for electrical recording from neurons usually have fewer wires than recording channels available to carry signals off the probe, which restricts the number of channels that can be recorded simultaneously. The authors propose to pool electrodes, using a single wire to serve many channels through a set of controllable switches.